I-ENTRE-U: an individual entrepreneurial orientation scale for teachers and researchers in higher education institutions - Felgueira, Teresa (2020)
Nowadays, something essential in Higher Education Institutions (HEI) is seeking to be entrepreneurial, with human resources with entrepreneurial characteristics. The success of higher education institutions will depend on the performance of its human resources. The main objective of this paper is to propose the concept of individual entrepreneurial orientation (IEO), based on the construct Entrepreneurial Orientation, a concept from the strategy-making literature, composed of five entrepreneurial dimensions (autonomy, innovativeness, risk taking, proactiveness, and competitive aggressiveness) (Lumpkin and Dess Academy of Management Review, 21(3), 605–607, 1996a; 135–172, b). The paper also proposes a measurement scale with a set of items, which are to measure the IEO of Teachers and Researchers in HEI. The EO will be measured by the ENTRE-U scale developed by Todorovic, McNaughton, and Guild in (Technovation, 31, 128–137, 2011) and adapted in this study to the individual level (I-ENTRE-U). A set of items is reviewed from the ENTRE-U, and the proposal scale adaptation was validated by academic experts. To test, debug and validate this measuring instrument, we used the confirmatory factor analysis (CFA), Pearson’s correlations and Cronbach’s alphas, among other measures. This paper conceptualizes the EO strategy, taking into account higher education peculiarities and discusses the dimensions of the IEO concept in HEI.